POLICY STREAM DALAM TAX AMNESTY UNDANG-UNDANG NOMOR 11 TAHUN 2016 - Subandi, Azwar; Pratama, Inka Nusamuda; Darmansyah, Darmansyah (Universitas Muhammadiyah Mataram, 2022)
The tax amnesty policy stream carried out by the Government is not optimal, this is based on the reference to Article 2 paragraph 2 contained in Law Number 11 of 2016, where the indicators are unstable domestic liquidity, not improving the rupiah exchange rate, not the extreme decline in interest rates, did not increase investment and a significant tax base. The purpose of this study is to look at the policy stream in the tax amnesty law number 11 of 2016. The method used is a qualitative research method by analyzing phenomena. The results of this study are that the tax amnesty policy stream carried out by the Government is not optimal, this is based on the reference to Article 2 paragraph 2 contained in Law Number 11 of 2016, where the indicator is unstable domestic liquidity, not the improvement in the rupiah exchange rate, no extreme decline in interest rates, no significant increase in investment and tax base.